2006
DOI: 10.1021/jf050914a
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Benzoxazinones and Derivatives and Microbial Activity in the Test Environment of Soil Ecotoxicological Tests on Poecilus cupreus and Folsomia candida

Abstract: Benzoxazinones, such as 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA) and 2,4-dihydroxy-1,4-benzoxazin-3-one (DIBOA), and benzoxazolinones, such as 6-methoxy-2-benzoxazolinone (MBOA) and 2-benzoxazolinone (BOA), are biologically active secondary metabolites found in cereals. Because these compounds could be exploited as part of a strategy for reducing the use of synthetic pesticides, ecotoxicological tests were performed recently. In this paper, the transformation of the compounds in the test environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…For example, recent experiments with cultivated fine fescue, sorghum species, and wheat have identified putative allelochemicals released from plant root exudates or residues, followed their degradation over time in soil settings, addressed their respective modes of action on higher plant growth, and identified bioactive allelochemicals or their metabolites at levels that could account for significant allelopathic interference in field settings (Nimbal et al 1996a, b;Bertin et al 2003;Dayan 2006;Macias et al 2006;Bertin et al 2007). Fomsgaard et al (2006) provide an excellent example of rigorous and well-documented method validation (i.e. reporting the inclusion of blanks, a standard curve, and recovery efficiencies from soil).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent experiments with cultivated fine fescue, sorghum species, and wheat have identified putative allelochemicals released from plant root exudates or residues, followed their degradation over time in soil settings, addressed their respective modes of action on higher plant growth, and identified bioactive allelochemicals or their metabolites at levels that could account for significant allelopathic interference in field settings (Nimbal et al 1996a, b;Bertin et al 2003;Dayan 2006;Macias et al 2006;Bertin et al 2007). Fomsgaard et al (2006) provide an excellent example of rigorous and well-documented method validation (i.e. reporting the inclusion of blanks, a standard curve, and recovery efficiencies from soil).…”
Section: Discussionmentioning
confidence: 99%
“…Many cereals produce the hydroxamic acids 2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3(4 H)-one (DIM-BOA) and 2,4-dihydroxy-1,4-benzoxazin-3(4 H)-one (DIBOA) (Niemeyer, 1988;Baumeler et al, 2000). The benzoxazolinones 6-methoxy-2-benzoxazolinone (MBOA) and 2-benzoxazolinone (BOA), interestingly enough, are the degradation products of DIMBOA and DIBOA, respectively (Fomsgaard et al, 2006). MBOA and BOA have been shown to be further transformed into 2-amino-7-methoxy-3 H-phenoxazin-3-one (AMPO) and 2-amino-3 H-phenoxazin-3-one (APO), respectively (Understrup et al, 2005).…”
Section: Increases In Allelochemical Toxicity Through Microbialmentioning
confidence: 99%
“…A highly toxic quinone responsible for walnut allelopathy is juglone (5,hydroxyl-1,4-naphthoquinone), which is also used in pharmacological studies (Gries, 1942;Kamei et al, 1998;Inbaraj and Chignell, 2004). Fomsgaard et al (2006) reported that cereals contain biologically active secondary metabolites such as the benzoxazinones [2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one (DIMBOA) and 2,4-dihydroxy-1,4-benzoxazin-3-one (DIBOA)] and the benzoxazolinones [6-methoxy-2-benzoxazolinone (MBOA) and 2-benzoxazolinone (BOA)]. The benzoxazolinones are found as degradation products of DIMBOA and DIBOA both in plants and in soil, respectively.…”
Section: Biochemical Naturementioning
confidence: 99%
“…During ecotoxicological tests, Fomsgaard et al (2006) found that DIMBOA was degraded and partly transformed to MBOA. Testing of MBOA on Poecilus cupreus media showed that at the initial concentrations of 2 and 10 mg kg -1 no MBOA was left after 45 days, but AMPO was formed, and on both Folsomia candida and Poecilus cupreus test media BOA was transformed to a biologically more active compound APO.…”
Section: Fate In Soilmentioning
confidence: 99%